Analisis Karakteristik Sastra Anak Yang Terdapat Dalam Kumpulan Cerpen Dan Dongeng Minuman Nusantara - Hesti Zulianti; Jajang Riyanto (Program Studi PGSD Kampus UPI di Serang, 2021)
This short story or often shortened to a short story is always related to the world's children. Likewise with fairy tales. Whether it is read only for children's own entertainment or also as teaching material for children's language and literature learning at school. There are also those in the children's short stories and fairy tales, which have differences with the criteria in short stories and tales of adolescents as well as adults. In this study, there is a location to describe the themes, plot, characters and backgrounds contained in children's literature in the form of a collection of short stories and tales of Indonesian beverages. This study uses a noninteractive qualitative research approach with content analysis methods. Then for the data procedure technique itself in this study using document analysis. The object in this research is a collection of short stories and tales of Indonesian beverages As for the instrument in this study is the researcher himself. As for analyzing the data, the researcher used the data analysis model of Miles and Huberman. Based on the results of the analysis on the collection of short stories and tales of Indonesian beverages, it has been found that the themes used in the six short stories and the fairy tales in it are the beauty of sharing, friendship, two stories with the same theme, namely love, and there are two more stories that have similar themes. beautiful colors are good. The plot used in the five forward plot stories where in each of the short stories and fairy tales there is no story that is repeated. Then there is one story that has a mixed plot, where in the story there is an event of the character reminiscing about what happened a few days ago. The characters in every short story and fairy tale mean humans, dwarves and fairies. Then for the background contained in each short story and the fairy tale itself about everyday life, namely in the palace, in the forest, at home, in the city, in the village and in a shop. Next, it is hoped that the results of this analysis can become a reference for literary research that analyzes themes, plot, characters and settings. Besides that, it can also be a reference as a teacher's teaching material in teaching short story analysis and fairy tales. Especially for teachers in elementary schools.